Reduction of Amides to Amines Catalyzed by Ca(CH2C6H4NMe2‐o)2(THF)2/HBpin - Liu, Xunqingze; Xie, Hongzhen; Luo, Yunjie (ChemistrySelect (Weinheim), 2023)
Reduction of amides to amines is an attractive subject in organic synthesis. Ca(CH2C6H4NMe2‐o)2(THF)2, an easily accessible main‐group complex, on combination with pinacolborane (HBpin) could serve as a highly active catalyst system in the reduction of primary, secondary and tertiary amides into the corresponding amines. This protocol showed good tolerance for functional groups and heteroatoms, and the aimed products could be obtained in a gram‐scale. The active species in this transformation was supposed to be a calcium hydride. Ca(CH2C6H4NMe2‐o)2(THF)2/HBpin can serve as a highly active catalyst system for the reduction of primary, secondary and tertiary amides into amines.